THE FIRST PRACTICE OF VIDEO RECORDING IN THE LABOR WARD - Иозефсон, Сергей Абрамович; Белокриницкая, Татьяна Евгеньевна; Агафонова, Елена Николаевна; Лига, Валентина Федоровна; Брум, Ольга Юрьевна (Mother and Baby in Kuzbass, 2017)
The aim of the research – video recording has become a reality in various spheres of everyday living. A medical practice is not an exception. The patients and their representatives take legal action for quality of health care delivery with increasing frequency. For an impartial assessment of the patients’ claims and delivery quality control video recording of delivery process was practiced. Materials and methods. The survey comprises the questionnaire of 72 patients and 20 medical workers of a maternity obstetric service concerning their attitude toward video recording in the delivery room. Results. 55.5 % of all women vote in the affirmative and 19.4 % countervote, every fourth patient was not sure. 70 % of doctors had a positive attitude to the video reordering. Conclusion. The article deals with the legal aspects of video reordering, both for patients and for medical staff. The study reveals a number of problems of ethical and legal aspects. In particular, the storage time of videos is limited to 15 days which does not make possible further later analysis. The present paper does not regulate a handover of video to patients.